Causal Relationship Between Epilepsy, Status Epilepticus and Sleep-Related Traits: A Bidirectional Mendelian Randomization Study - Yong-Won Shin; Sang Bin Hong (Brain Sciences, 2025)
Background/Objectives: Epilepsy and sleep disturbances frequently co-occur, yet the causal nature of this relationship remains uncertain, particularly in relation to epilepsy subtypes and status epilepticus. We investigated potential bidirectional causal associations between sleep-related traits and epilepsy, including subtypes and status epilepticus, using Mendelian randomization (MR). Methods: We conducted two-sample MR using genome-wide association study (GWAS) summary statistics from European ancestry cohorts. Epilepsy, its subtypes, and status epilepticus were analyzed using data from the International League Against Epilepsy Consortium on Complex Epilepsies (ILAE) and the FinnGen study. Nine self-reported sleep-related traits were derived from the UK Biobank-based GWAS. Causal estimates were primarily obtained using inverse variance weighted models with additional MR analysis methods. Pleiotropy and heterogeneity were assessed to enhance the robustness of the finding. Results: Several subtype-specific associations were identified, with direction and statistical significance varying across cohorts and subtypes. After correction for multiple testing and filtering for tests with ≥10 instrumental variables to ensure robust and reliable MR estimates, several consistent and potentially mutually reinforcing associations emerged. In the ILAE cohort, focal epilepsy with hippocampal sclerosis was associated with an increased risk of insomnia, and juvenile myoclonic epilepsy with reduced sleep duration. In the FinnGen cohort, overall epilepsy was associated with increased risk of both insomnia and daytime sleepiness. In reverse MR, daytime sleepiness and napping were associated with increased risk of epilepsy, while daytime napping and frequent insomnia symptoms were linked to elevated risk of status epilepticus. Conclusions: Our findings reveal subtype-specific and bidirectional causal links between epilepsy and sleep-related traits. These results highlight the biological interplay between epileptic networks and sleep regulation and underscore the need for further clinical and mechanistic studies.